2006
DOI: 10.1096/fj.06-6304fje
|View full text |Cite
|
Sign up to set email alerts
|

The calcium sensing receptor is directly involved in both osteoclast differentiation and apoptosis

Abstract: Intracellular transduction pathways that are dependent on activation of the CaR by Ca(o)2+ have been studied extensively in parathyroid and other cell types, and include cytosolic calcium, phospholipases C, A2, and D, protein kinase C isoforms and the cAMP/protein kinase A system. In this study, using bone marrow cells isolated from CaR-/- mice as well as DN-CaR-transfected RAW 264.7 cells, we provide evidence that expression of the CaR plays an important role in osteoclast differentiation. We also establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(141 citation statements)
references
References 49 publications
5
133
0
3
Order By: Relevance
“…Strontium acts on the CaSR as a full agonist with lower affinity than calcium [31,32]. There is some evidence that osteoclast precursor cells and osteoclasts express the parathyroid CaSR [33,34]. Interestingly, this receptor mediates the increased osteoclast apoptosis induced by SrRan [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strontium acts on the CaSR as a full agonist with lower affinity than calcium [31,32]. There is some evidence that osteoclast precursor cells and osteoclasts express the parathyroid CaSR [33,34]. Interestingly, this receptor mediates the increased osteoclast apoptosis induced by SrRan [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this receptor mediates the increased osteoclast apoptosis induced by SrRan [35]. Finally, both calcium and strontium were found to act on osteoclast precursor cells via the CaSR [34,36]. In addition, strontium, decreased the expression of sclerostin, an osteocyte specific secreted protein that acts as a negative regulator of bone formation by inhibiting canonical Wnt signaling, hence strentium expected to increase canonical Wnt signalling that stimulates osteoblastic proliferation, differentiation and function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports witness that CaSR-mediated apoptosis, through mechanisms related with calcium overload and activation of the mitochondrial apoptotic pathways, involves the downregulation of Bcl-2 expression, and upregulation of caspase-3, cytochrome c and Fas/FasL expression [54][55][56][57][58][59]. Importantly, Mentaverri et al reported that NF-B activation, which promotes expression of cell death genes such as p53, c-Myc and Bcl-xS, is a downstream effect of CaSR stimulation in mature rabbit osteoclasts [60]. Phosphorylation of ERK regulates cell growth and differentiation through phosphorylation and activation of nuclear TFs, such as Elk-1.…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…RANKL triggers downstream signalling pathways such as the NF‐κB pathway, mitogen‐activated protein kinase (MAPK) (extracellular signal‐regulated kinase [ERK], p38, and c‐Jun N‐terminal kinase [JNK]) pathway to induce the expression of osteoclastic key transcriptional factors such as c‐Fos and nuclear factor of activated T‐cells 1 (NFATc1), finally inducing the formation of functional mature osteoclasts 10. In addition, these cytokines are also required to stimulate and maintain the differentiation, survival, and apoptosis of osteoclasts by modulating the mitochondrial pathway (Bcl‐2/Bax) and the death receptor pathway (caspases) 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%